Tindak Penghasutan Dalam Pasal 160 KUHP Pasca Putusan Mahkamah Konstitusi Nomor 7/PUU-VII/2009 - Toufan Hazmi Haidi (Jurist-Diction, 2022)
AbstractIncitement is an act that has been regulated in the Criminal Code which is itself an adaptation of Wetboek Van Strafrecht Nederland so that there are still colonial articles, one of which is Article 160 which regulates sedition. The Constitutional Court has conducted an examination of Article 160 of the Indonesian Criminal Code in its decision to formulate the original formal offense into a material formulation. This research aims to explain the Qualifications of incitement criminal offenses based on statutory regulations and the basic considerations of the Constitutional Court which formulates the incitement criminal offenses as material offenses. The results of this study indicate that inciting is different from persuasion, where persuading there are endeavors that must be fulfilled such as by giving gifts, promises, abusing power, abusing position, using the threat of convenience and deception, whereas instigation has a clear and devoid of endeavors namely to committing criminal acts, committing violence against public authorities or not complying with both the provisions of the law and the position orders given based on the law. Keywords: Incitement; Material Offense. AbstrakPenghasutan merupakan suatu perbuatan yang telah diatur dalam KUHP yang mana KUHP sendiri merupakan saduran dari Wetboek Van Strafrecht Nederland sehingga masih terdapat pasal bersifat kolonial dimana salah satunya adalah Pasal 160 yang mengatur penghasutan. Mahkamah Konstitusi telah melakukan pengujian terhadap Pasal 160 KUHP dalam putusannya perumusan yang semula delik formil menjadi perumusan materiil. Penelitian ini bertujuan untuk menjelaskan Kualifikasi tindak pidana penghasutan berdasarkan peraturan perundang-undangan dan Dasar pertimbangan Mahkamah Konstitusi yang merumuskan tindak pidana penghasutan sebagai delik materiil. Hasil dari penelitian ini menunjukan bahwa menghasut berbeda dengan membujuk, dimana membujuk ada ikhthiar yang harus dipenuhi seperti dengan memberikan pemberian, janji-janji, menyalahgunakan kekuasaan, menyalahgunakan kedudukan, menggunakan kerasan ancaman dan muslihat, sedangkan menghasut memiliki tujuan yang jelas dan tanpa ikhtiar yaitu untuk melakukan perbuatan pidana, melakukan kekerasan terhadap penguasa umum atau tidak menuruti baik ketentuan undang-undang maupun perintah jabatan yang diberikan berdasar undang-undang.Kata Kunci: Penghasutan; Delik Materiil.